The Influence Out-Of-Wedlock Birth on Child Custody in Gunungkidul, Yogyakarta: A Sosio-Legal Analysis - Krismono, Krismono; Dzulfikar Rahman, Rabik (Qanun: Jurnal Hukum Keluarga Islam, 2024)
This study explores the impact of out-of-wedlock births on child custody rights in Gunungkidul, Yogyakarta through a socio-legal approach. In this area, out-of-wedlock pregnancies are common among teenagers, creating social and legal challenges in regulating child custody rights. Using qualitative case study research, data were gathered through interviews and literature review. The main findings indicate that the unclear status of children and the teenagers' lack of preparedness in facing pregnancy significantly impact the legalization process and increase social stigma towards both teenagers and their children. The study reveals deficiencies in sexual education and social support, as well as a mismatch between social values and the existing legal framework. Recommendations include urgent policy reforms to prioritize children's rights and provide greater protection for teenagers. Expanded strategies for sexual education and socialization are also recommended to prevent out-of-wedlock pregnancies. The implications of these findings are expected to improve legal practices and social handling related to the custody rights of children born from out-of-wedlock relationships in Gunungkidul, Yogyakarta.